Multiomics analysis of metabolic heterogeneity in cervical cancer cell lines with or without HPV - Liu, Xu; Zhu, Yaqi; Huang, Sheng; Shi, Tingyu; Li, Tanghua; Lan, Yanan; Cao, Xiaojian; Wu, Yingtao; Ding, Jinya; Chen, Xiaohua (Frontiers in Oncology, 2023)
Metabolomics analysis revealed the metabolic heterogeneity of cervical cancer (CC) cell lines C33A and CaSki, and their molecular mechanisms were explored. Using the modified Bligh-Dyer method, the endogenous metabolites of C33A and CaSki cells were divided into polar and nonpolar fractions. The metabolites were analysed by ultra-performance liquid chromatography-quadrupole-time-of-flight 带格式的 2 mass spectrometry (UPLC-Q-TOF-MS). Then, the differential metabolites were screened by combining multivariate statistical analysis and volcano maps, and functional enrichment and pathway analysis of the differential metabolites were performed. Finally, association analysis was carried out in combination with transcriptomics, and the important differential metabolisms were experimentally verified by real-time PCR (RT-qPCR) and oil red staining. The results showed that between the C33A and CaSki cell lines, there were significant differences in amino acids, nucleotides and lipids, such as in threonine, arachidonic acid and hypoxanthine, in the metabolic pathways. These compounds could be used as markers of differences in cellular metabolism. The heterogeneity of lipid metabolism accounted for 87.8%, among which C33A cells exhibited higher contents of fatty acid polar derivatives, while CaSki cells showed higher contents of free fatty acids and glycerides. Based on correlation analysis of the above metabolic differences in HPV pathways as well as lipid metabolism-related genes, p53 and the genes involved in lipid metabolism pathways, such as Peroxisome Proliferator Activated Receptor Gamma(PPARG) and stearoyl-CoA desaturase (SCD), are relevant to the metabolic heterogeneity of the cells. The differential expression of some genes was validated by RT-qPCR. CaSki cells showed significantly higher glyceride levels than that of C33A cells, as verified by oil red O staining and glyceride assays. The above results showed that the metabolomic differences between C33A and CaSki cells were relatively obvious, especially in lipid metabolism, which might be related to the decreased expression of PPARG and p53 caused by HPV E6. Further studies on the molecular mechanism of lipid metabolism heterogeneity in cervical cancer cell lines with or without HPV could provide a new reference for the development of CC and individualized treatments of tumour patients.